Predicting neonatal outcomes in infants with giant omphalocele using prenatal magnetic resonance imaging calculated observed‐to‐expected fetal lung volumes. (9th September 2021) - Danzer, Enrico; Edgar, J. Christopher; Eppley, Elizabeth; Goldshore, Matthew A.; Chotzoglou, Etze; Herkert, Lisa M.; Oliver, Edward R.; Rintoul, Natalie E.; Panitch, Howard; Adzick, N. Scott; Hedrick, Holly L.; Victoria, Teresa
Abstract: Objective: To examine the association between prenatal magnetic resonance imaging (MRI) based observed/expected total lung volume (O/E TLV) and outcome in neonates with giant omphalocele (GO). Methods: Between 06/2004 and 12/2019, 67 cases with isolated GO underwent prenatal and postnatal care at our institution. MRI‐based O/E TLVs were calculated based on normative data from Meyers and from Rypens and correlated with postnatal survival and morbidities. O/E TLV scores were grouped based on severity into <25% (severe), between 25% and 50% (moderate), and >50% (mild) for risk stratification. Results: O/E TLV was calculated for all patients according to Meyers nomograms and for 49 patients according to Rypens nomograms. Survival for GO neonates with severe, moderate, and mild pulmonary hypoplasia based on Meyers O/E TLV categories was 60%, 92%, and 96%, respectively ( p = 0.04). There was a significant inverse association between Meyers O/E TLV and risk of neonatal morbidities ( p < 0.05). A similar trend was observed with Rypens O/E TLV, but associations were less often significant likely related to the smaller sample size. Conclusion: Neonatal outcomes are related to fetal lung size in isolated GO. Assessment of Meyers O/E TLV allows identification of GO fetuses at greatest risk for complications secondary to pulmonary hypoplasia. Key points: What is already known about this topic? Accurate prenatal assessment of the severity of pulmonary hypoplasia in giant omphalocele (GO) fetus is limited What does this study add? Prenatal magnetic resonance imaging (MRI) evaluation of observed/expected total lung volume (O/E TLV) is a useful adjunct in the assessment of GO fetuses Postnatal survival and morbidities are related to the fetal lungs size in isolated GO Categorizing lung size as mild, moderate, and severe provides a way to predict prenatally GO fetuses that are at the greatest risk for postnatal complications